DEVELOPING WRITING SKILLS THROUGH DREAM-THEMED POETRY: AN INTEGRATIVE TEST APPROACH FOR 10TH-GRADE SENIOR HIGH SCHOOL STUDENTS - Hidayah, Adilah Nurul (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Literature education at the senior high school level, particularly in poetry writing, requires students to select diction that is both aesthetically pleasing and meaningful. This study aims to describe the process of teaching poetry writing on the theme of ‘dreams’ using the Integrative Test approach. The research employs a descriptive qualitative method, with the primary data consisting of authentic poems written by 10th-grade students. The instructional process guides students to explore vocabulary through a language corpus before composing their poems. The analysis reveals that students were able to metaphorically express the concept of “dreams” using various diction choices that reflect beauty, light, grandeur, and the value of perseverance. These lexical selections indicate a depth of understanding fostered by meaningful, data-driven learning experiences. The findings suggest that integrating the Integrative Test approach with corpus-based learning resources can enhance the quality of students’ literary expression.